The Role of Hydraulic Failure in a Massive Mangrove Die-Off Event - Gauthey, Alice; Backes, Diana; Balland, Jeff; Alam, Iftakharul; Maher, Damien T.; Cernusak, Lucas A.; Duke, Norman C.; Medlyn, Belinda E.; Tissue, David T.; Choat, Brendan (Frontiers in Plant Science, 2022)
Between late 2015 and early 2016, more than 7000 ha of mangrove forest died along the coastline of the Gulf of Carpentaria, in northern Australia. This massive die-off was preceded by a strong 2015/2016 El Niño event, resulting in lower precipitation, a drop in sea level and higher than average temperatures in northern Australia. In this study, we investigated the role of hydraulic failure in the mortality and recovery of the dominant species, Avicennia marina, two years after the mortality event. We measured predawn water potential (WPpd) and stem percent loss of stem hydraulic conductivity (PLC) in surviving individuals across a gradient of impact. We also assessed the vulnerability to drought-induced embolism (P50) for the species. Areas with severe canopy dieback had higher native PLC (39%) than minimally impacted areas (6%), suggesting that hydraulic recovery was ongoing. The high resistance of A. marina to drought-induced embolism (P50 = -9.6 MPa), indicates that severe water stress (WPpd < -10 MPa) would have been required to cause mortality in this species. Our data indicate that the natural gradient of water-stress enhanced the impact of El Niño, leading to hydraulic failure and mortality in A. marina growing on severely impacted (SI) zones. It is likely that lowered sea levels and less frequent inundation by seawater, combined with lower inputs of fresh water, high evaporative demand and high temperatures, led to the development of hyper-salinity and extreme water stress during the 2015/16 summer.